Anterior Cruciate Ligament Stability in Soft-Embalmed Cadaver vs In vivo Knee: Alternative Approaches to Medical Education - Millar WA; Armstrong LR; Becker RM; Musick AN; Ryan DB; Kwasigroch TE (Advances in Medical Education and Practice, 2023)
William A Millar, Landon R Armstrong, Robert M Becker, Adam N Musick, David B Ryan, Thomas E Kwasigroch Department of Medical Education, James H. Quillen College of Medicine, East Tennessee State University, Johnson City, TN, USACorrespondence: Thomas E Kwasigroch, Department of Medical Education, James H. Quillen College of Medicine, PO Box 70582, Johnson City, TN, 37614, USA, Tel +1 (423) 239-2006, Email kwasigro@mail.etsu.eduIntroduction: Soft-embalmed cadavers have been used in medical education with a variety of success in different curriculum objectives. In the United States, the ACL is the most commonly injured ligament. Yet, there has been little focus on the stability of the knee in the sagittal plane provided by the anterior cruciate ligament within the soft-embalmed cadaver model. If the soft-embalmed cadaver ligaments contain similar elastic properties as an in-vivo knees, this will offer yet another means for further advancements in medical education to detect and assess musculoskeletal injuries.Purpose: Evaluate how similarly the anterior tibial translation of soft-embalmed cadaver anterior cruciate ligaments compares to in-vivo tissue.Methods: The KT-1000 arthrometer was used to assess the laxity of the anterior cruciate ligament of thirteen soft-embalmed cadavers consisting of five females and eight males with a mean age of 79.3 years and duration of time since embalming ranging from 250 to 1156 days. Anterior displacement of the tibia in relation to the femur was registered at 67N and 89N. The soft-embalmed cadaver measurements were compared against twenty-one healthy uninjured individuals whose anterior tibial translation was measured using the same process. Data sets were analyzed using a welch two-sample t-test to determine the similarity between the means of the data sets.Results: The t-tests proved a significant difference between live and soft-embalmed cadaver knees. The anterior tibial translation in the set of healthy live knees directly compared to the soft-embalmed cadaver group for 67N depicts an average difference of 1.76mm. The same comparison at 89N depicts an average difference of 2.12mm.Conclusion: While soft-embalmed cadavers may not directly replicate ATT to an exact number to that of in vivo tissue, they still allow the perception of the tibial translation against a stationary femur. The difference is less than 2.5 mm in both data sets when compared to an in-vivo knee, equivalent to one-tenth of an inch. Suggesting the viability of soft-embalmed cadavers ATT and should not exclude their use in medical education.Keywords: medical education, anatomy, anterior cruciate ligament, soft-embalmed cadaver